The Correlation between Perfectionism and Fear of Failure among Students in Intensive Arabic Language Program | Al-'Alaqah bayna al-Kamaliyyah wa al-Khawf min al-Fashl li-Tullab al-Barnaamij al-Mukaththaf li-Ta'lim al-Lughah al-'Arabiyyah - M Abdul Hamid; Nur Ila Ifawati; M Abdullah Charis (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2024)
This study aims to describe the classification of perfectionism and fear of failure, as well as the relationship between these two factors in Arabic language learning among students in the intensive program at Maulana Malik Ibrahim University in Malang. This quantitative correlational study utilized a Google Form survey and data analysis using Pearson